Parenting and mobile phone addiction tendency of Chinese adolescents: The roles of self-control and future time perspective - Peng, Yuan; Wang, Yali; Liu, Shaozhuo; Hu, Xingzhao (Frontiers in Psychology, 2022)
Previous studies examined the impact of parenting on adolescents' mobile phone addiction tendencies. However, relatively few studies examined the potential mechanism underlying such a relationship. Thus, the present study further explored the mediation effect of self-control and the moderating effect of future time perspective between parenting and mobile phone addiction tendencies of Chinese adolescents. A sample of 1,349 Chinese adolescents (Mage = 15. 22 years, SD = 0.79) responded to the anonymous questionnaires regarding parenting, including parental control and parental care, self-control, future time perspective, and mobile phone addiction tendency. The results showed that (1) parental control was positively related to adolescents' mobile phone addiction tendencies, while parental care was negatively related to adolescents' mobile phone addiction tendencies; (2) self-control could mediate the pathway from both parental control and parental care to adolescents' mobile phone addiction tendencies; and (3) the indirect pathway could be moderated by future time perspective. Specifically, a high future time perspective combined with high self-control predicted a low level of mobile phone addiction tendency. In contrast, low self-control was associated with a high tendency toward mobile phone addiction, regardless of their future time perspective. The present study revealed a complex interplay between family and individual factors contributing to adolescents' mobile phone addiction tendencies.